Cationic Iron(III) Porphyrin Catalyzed Dehydrative Friedel–Crafts Reaction of Alcohols with Arenes - Teranishi, Satoru; Kurahashi, Takuya; Matsubara, Seijiro (Synlett, 2013)
Alcohols react with arenes in the presence of cationic iron(III) porphyrin catalyst. The reaction involves the formation of the C–C bond via dehydration, which is formal Lewis acid catalyzed Friedel–Crafts reaction.
Keywords: alcohols; arenes; coupling; iron; porphyrins